2018
DOI: 10.33687/ijae.006.01.2301
|View full text |Cite
|
Sign up to set email alerts
|

Factors impeding citrus supply chain in Central Punjab, Pakistan

Abstract: Pakistan is one of the largest citrus producer and leading exporter of Kinnow in world. Average production of this vital fruit comparatively lower than potential and in result, minor contributions comes to national economy and livelihoods of the growers. Present study was designed to analyze factors impeding citrus supply chain in Toba Tek Singh District of the Punjab province. Through multistage sampling technique 120 citrus growers were selected. Data were collected through face to face interview technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 3 publications
3
18
0
Order By: Relevance
“…After a thorough review of these studies, the 30 constraints that we identified in the FGDs were sub-divided into two distinct categories, i.e., production and marketing constraints. These listed production and marketing constraints were also supported by the literature as they are well documented in previous research (e.g., [11,12,24,33,36]), and therefore are more applicable. For example, inadequate extension and technical information, poor quality of improved nursery plants, irrigation water shortages, infestations of disease, pest attack, and climate change are frequently acknowledged in previous studies affecting supply chain participation by farmers [12].…”
Section: Identification Of Constraintssupporting
confidence: 76%
See 3 more Smart Citations
“…After a thorough review of these studies, the 30 constraints that we identified in the FGDs were sub-divided into two distinct categories, i.e., production and marketing constraints. These listed production and marketing constraints were also supported by the literature as they are well documented in previous research (e.g., [11,12,24,33,36]), and therefore are more applicable. For example, inadequate extension and technical information, poor quality of improved nursery plants, irrigation water shortages, infestations of disease, pest attack, and climate change are frequently acknowledged in previous studies affecting supply chain participation by farmers [12].…”
Section: Identification Of Constraintssupporting
confidence: 76%
“…For example, Johnson [25] estimated that these losses were about 40% in Pakistani citrus fruit. Some studies have shown that 35% of Pakistan's total citrus production is lost in the process of supplying fruit from one place to another [12]. The percentage of total post-harvest losses is even higher at the farmer level [26].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is termed as alternate bearing to affect citrus orchard productivity and profitability (Davis et al, 2004) along with marketing issues like superfluity; uneven supply and price oscillation (Moss et al, 1974). In Pakistan, biennial bearing impinge on supply-chain by recording 40% (Johnson, 2006) and 35% fruit loss (Khan, 2008) with recoding more profit margin of brokers, buyers and exporters during heavy bearing season (Usman et al, 2018).…”
Section: /11mentioning
confidence: 99%